2020
DOI: 10.1186/s13071-020-3988-4
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Dirofilaria immitis antigen and antibodies to Leishmania infantum and Toxoplasma gondii in cats from Madeira Island, Portugal

Abstract: Background: Dirofilaria immitis, Leishmania infantum and Toxoplasma gondii are zoonotic parasites which can affect domestic cats. Considering the lack of published data from the local feline population, this study aimed to assess infection with or exposure to these pathogens in cats from Madeira Island, Portugal. Methods: One hundred and forty-one domestic cats (77 males and 64 females; median age: 2 years) were sampled at a veterinary medical centre in Funchal, from September 2018 to January 2019. Serum sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…The Mediterranean basin is a suitable environment for the circulation of VBDs in domestic animals; thus, monitoring local canine populations and updated epidemiological data are crucial because available information is often limited to specific countries or to selected pathogens [15,[22][23][24]. Recent studies have demonstrated that several zoonotic VBDs are shared between dog and cat populations throughout the Mediterranean basin, inevitably increasing the chances of spreading among pet populations and transmission to people [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean basin is a suitable environment for the circulation of VBDs in domestic animals; thus, monitoring local canine populations and updated epidemiological data are crucial because available information is often limited to specific countries or to selected pathogens [15,[22][23][24]. Recent studies have demonstrated that several zoonotic VBDs are shared between dog and cat populations throughout the Mediterranean basin, inevitably increasing the chances of spreading among pet populations and transmission to people [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, male cats were more exposed to T. gondii than females. However, Neves et al [58] and Pereira et al [61] found no association between sex and the presence of anti-T. gondii antibodies in other feline populations. According to Miró et al [52] and Smith et al [74], due to the explorative behavior of males, they end up being more prone to T. gondii infection than females.…”
Section: Discussionmentioning
confidence: 94%
“…High anti-T. gondii antibody frequencies have been reported in domestic dogs and cats from Cuba, Mexico, Panama, Iran, Argentina, Portugal, Australia, Colombia, and Chile [1,10,26,30,44,57,58,63,83,86]. In Brazil, the frequency of T. gondii infection in Brazilian pet animal populations can vary from 9 to 70% in dogs and from 0 to 71% in cats [5,9,35,47,50,68,81].…”
Section: Introductionmentioning
confidence: 99%
“…f Molecular (nPCR, ITS) Buffy coat 12.0 ( L. donovani s.l .) 4.0 ( L. major ) Neves et al. (2020) 2018–2019 F. catus (domestic) 141 Serological (DAT, 1:100) Serum 0 Vilhena et al.…”
Section: Aetiology Distribution and Risk Factorsmentioning
confidence: 99%